Language Learning Strategies Post Covid-19 Trough Online Learning (A Library Research) - Yude, Uswatun Hasanah (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
During the COVID-19 pandemic, online learning has brought to light the importance of digital technology-based education. As a reference for developing a learning pattern following the COVID-19 pandemic, the purpose of the article was to examine the effectiveness of online learning at bachelor's, master's, and doctoral degrees in Islamic Religious Education. A concurrent triangulation model and a mixed-methods design were used in the study. Purposive and stratified random sampling were used to collect the samples. In the meantime, questionnaires, in-depth interviews, and forum group discussions were used to collect the data. The qualitative data were subjected to interpretative descriptive analysis, while the quantitative data were subjected to descriptive analysis and one-way analysis of variance. The study demonstrated that online learning at the bachelor's, master's, and doctoral levels in Islamic Religious Education during the COVID-19 pandemic was successful. Online doctoral education was the most effective of all. However, face-to-face instruction is still required. As a result, the post-COVID-19 pandemic learning pattern combines in-person and online learning (hybrid learning).At each educational level, the formulation is modified in accordance with the characteristics, educational purpose and orientation, level of ability, readiness, and learning autonomy of the students.